Ceramic rock plate with starlight effect and preparation method thereof
By applying a starlight glaze layer composed of specific minerals on the surface of the ceramic rock slabs to form high refractive index crystals, the problems of poor starlight effects and insufficient wear resistance and anti-fouling performance in the prior art are solved, and three-dimensional and high Abrasion-resistant and anti-fouling performance starlight effect.
Patent Information
- Application Number
- CN202411709181.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-02-21
AI Technical Summary
In the prior art, the preparation method of starlight effect ceramic tiles has problems such as lack of three-dimensionality and layering of the flash points, unreal flash effects, easy to absorb dirt and inconvenient cleaning.
Using astroscope glaze layer composed of basic glaze, magnesium-containing minerals, calcium-containing minerals, iron trioxide and zinc oxide, the high temperature firing makes these elements react chemically with silicates to form high refractive index crystals to achieve The starlight effect of the glaze surface and improves wear resistance and stain resistance.
It realizes the starlight effect on the surface of the ceramic rock slab, has a good three-dimensional sense and layering sense, and at the same time improves the hardness, wear resistance and stain resistance of the glaze.
Smart Images

Figure CN119490349A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of building ceramics, and in particular relates to a ceramic rock plate with a starlight effect and a preparation method thereof. Background Art
[0002] In recent years, with the improvement of living standards, people have higher and higher requirements for the decoration of ceramics and other products. The decorative effect of ceramic tiles with starlight effect can change with different lighting and viewing angles, and has attracted more and more attention. The effect is mainly presented by forming sparkling particles on the surface of the tile, like diamonds or stars and galaxies in the night sky. Today, the advantage of star diamond flash ceramic tiles is that the texture of the tile is full of shining texture, just like buying the starry sky and galaxy home, enjoying the romantic atmosphere of the house.
[0003] At present, there are four main methods for preparing ceramic tiles with starlight effects: the first is to use glaze dry particles of different particle sizes and different high temperature resistance combined with a semi-polishing process to achieve a flashing effect on the surface of the glaze layer; the second is to introduce flashing mica into the glaze to achieve a flashing effect of the glaze layer; the third is to directly introduce specific zircon sand into the glaze layer to achieve the flashing of the glaze layer; the fourth is to evenly distribute the flashing dry particles on the surface of the brick, fix the flashing dry particles with glue, and burn them in a kiln to achieve a flashing effect of the glaze layer. In the above preparation methods, the first flash point is on the surface of the glaze layer, lacking a three-dimensional sense and a sense of layering, and the decorative effect is not good. The second ceramic tile that uses mica to achieve a glazed starlight flashing effect is always not real enough, and cannot achieve a diamond-like or starlight-like flashing effect of stone-like grains under light. The third method of directly using zircon sand to achieve a flashing effect has the problem that white bricks are more dirty, and ceramic tiles have the problem of easy dirt absorption on the brick surface. The fourth method uses glue to fix the flash dry particles and then fires them. The surface of the prepared ceramic tiles is raised, which is easy to get dirty and difficult to clean. At the same time, during the preparation process, the excess dry particles need to be sucked away, and the process is difficult to control. Summary of the invention
[0004] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a ceramic rock plate with starlight effect and a preparation method thereof, wherein a large number of glitter particles are evenly distributed on the surface of the ceramic rock plate, which has a starlight effect and has good wear resistance and anti-fouling properties.
[0005] To solve the above technical problems, the first aspect of the present invention provides a ceramic rock plate, which includes, from bottom to top, a body layer, a surface glaze layer, a pattern decoration layer and a starlight glaze layer, wherein the raw materials for preparing the starlight glaze layer contain basic glaze, magnesium-containing minerals, calcium-containing minerals, ferric oxide and zinc oxide.
[0006] Specifically, a layer of starlight glaze is applied on the surface of the ceramic rock plate of the present invention. In addition to the basic glaze, the raw materials for preparing the glaze layer also contain a certain amount of magnesium-containing minerals, calcium-containing minerals, ferric oxide and zinc oxide, which provide Fe, Mg, Ca, Zn and other metal elements for the basic glaze. These elements will react chemically with the silicate in the basic glaze during high-temperature firing, and precipitate from the glaze melt during the cooling stage to form crystals such as pyroxene crystals, zinc spinel, mullite, zinc oxide, etc. The refractive index of these crystals is relatively high, and the refractive index difference with the glass glaze is large, so it can present a shining starlight effect under lighting conditions. At the same time, crystals with relatively higher refractive index, such as zinc oxide and zinc spinel, produce stronger refractive effect on light; while crystals with relatively lower refractive index, such as pyroxene crystals and mullite, will produce relatively weak refractive effect. The refractive effect of different intensities makes the glaze surface produce a refractive effect of light and dark. In addition, the crystals are of different sizes and shapes, which makes the starlight effect rich in three-dimensional sense and layered sense. In addition, the precipitation of various crystals is beneficial to improving the hardness, wear resistance and anti-fouling properties of the glaze.
[0007] In some embodiments of the present invention, the magnesium-containing minerals include burnt talc and magnesite, and the mass ratio of the burnt talc to the magnesite is (4-15): 1. On the one hand, the magnesium-containing minerals are beneficial to promote the formation of pyroxene crystals and enhance the starlight effect of the glaze; on the other hand, burnt talc and magnesite are beneficial to reduce the firing temperature, form a liquid phase at a lower temperature, and accelerate the growth of crystals in the glaze melt.
[0008] In some embodiments of the present invention, the calcium-containing mineral is selected from at least one of calcite, limestone, and dolomite. The main component of these calcium-containing minerals is CaCO3, which is also conducive to promoting the formation of pyroxene crystals and enhancing the starlight effect of the glaze surface; at the same time, CaCO3 acts as a flux after high-temperature decomposition, which is conducive to improving the fluidity of the glaze melt and improving the anti-fouling performance of the glaze surface.
[0009] In some embodiments of the present invention, the basic glaze comprises feldspar, quartz and clay, and the mass ratio of the feldspar, quartz and clay is (2-5):(2-4):1.
[0010] In some embodiments of the present invention, the raw materials for preparing the starlight glaze layer include, by weight: 65-77 parts of basic glaze, 9-18 parts of magnesium-containing minerals, 10-15 parts of calcium-containing minerals, 1-2 parts of ferric oxide, and 1-3 parts of zinc oxide. By adjusting the ratio of each raw material in the glaze layer, a more suitable number and size of crystals can be formed, thereby achieving the best starlight effect.
[0011] In some embodiments of the present invention, the chemical composition of the surface glaze layer includes, by weight percentage: SiO2 55-60%, Al2O3 28-32%, Fe2O3 0.1-0.3%, TiO2 0.01-0.02%, CaO 0.6-0.8%, MgO 0.1-0.3%, K2O 1-2%, Na2O 2-4%, ZrO2 0.5-1%, ZnO 1-3%, and ignition loss 2-5%. The surface glaze layer has a glass phase earlier than the starlight glaze layer during the firing process, which is beneficial to the flatness of the starlight glaze layer.
[0012] In some embodiments of the present invention, the thickness of the starlight glaze layer is 0.6-1.0 mm. Using a thicker thickness than ordinary ceramic glaze layers is not only conducive to improving the flatness of the glaze layer, but also conducive to the precipitation of crystals in the glaze layer, thereby improving the layering and three-dimensional sense of the starlight effect.
[0013] The present invention has no special requirements on the raw material components of the green body layer, and conventional ceramic rock slab green bodies can be used.
[0014] The second aspect of the present invention provides a method for preparing the above-mentioned ceramic rock plate, comprising the following steps:
[0015] (1) taking raw materials for preparing the green body layer, preparing powder, and subjecting the powder to dispensing, molding, and drying to obtain the green body layer;
[0016] (2) Applying a top glaze, an inkjet-printed pattern, and a starlight glaze in sequence on the surface of the green body layer to form a top glaze layer, a pattern decoration layer, and a starlight glaze layer in sequence, and then drying and firing to obtain the ceramic rock slab.
[0017] In some embodiments of the present invention, the firing atmosphere is a reducing atmosphere. The raw materials for preparing the starlight glaze layer of the present invention contain a certain amount of Fe2O3, and the sintering is carried out in an oxidizing atmosphere. 3+ It will have a certain impact on the color of the glaze; in an oxygen-reducing atmosphere, the Fe in Fe2O3 3+ Will be reduced to Fe 2+ , which is beneficial to weaken Fe 3+ Adverse effects on the glaze.
[0018] In some embodiments of the present invention, the firing temperature regime is: first increase the temperature to 1230-1280°C at a heating rate of 10-15°C / min, and keep warm for 10-15 minutes; then cool to 800-900°C at a rate of 6-8°C / min, keep warm for 30-40 minutes, and finally cool naturally after leaving the kiln.
[0019] Specifically, the present invention firstly increases the temperature to the highest firing temperature at a relatively fast heating rate, and keeps the temperature for a certain period of time, so that the crystals exist in the glaze layer in the form of nano-scale microcrystals; then cools down at a relatively slow cooling rate, and keeps the temperature at the nucleation growth temperature of the crystals, so that a large number of evenly distributed microcrystals are precipitated in the glaze layer, thereby improving the starlight effect of the glaze and enhancing the wear resistance and anti-fouling properties of the glaze.
[0020] Compared with the prior art, the above technical solution of the present invention has at least the following technical effects or advantages:
[0021] The present invention applies a layer of starlight glaze on the surface of the ceramic rock plate. In addition to the basic glaze, the raw materials for preparing the glaze layer also contain a certain amount of magnesium-containing minerals, calcium-containing minerals, ferric oxide and zinc oxide, which provide metal elements such as Fe, Mg, Ca, and Zn to the basic glaze. These elements will react chemically with the silicate in the basic glaze during high-temperature firing, and precipitate from the glaze melt in the cooling stage to form pyroxene crystals, zinc spinel, mullite, zinc oxide and other crystals. These crystals present a shining starlight effect under lighting conditions. At the same time, crystals with relatively higher refractive indexes produce stronger refraction effects on light, while crystals with relatively lower refractive indexes produce relatively weaker refraction effects. The refraction effects of different intensities make the glaze surface produce a refraction effect of light and dark alternating; in addition, the crystals are of different sizes and shapes, which makes the starlight effect rich in three-dimensionality and layering. In addition, the precipitation of multiple crystals greatly improves the hardness, wear resistance and anti-fouling properties of the glaze. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 This is a physical picture of the ceramic rock slab prepared in Example 1 of the present invention. DETAILED DESCRIPTION
[0023] The present invention is described in detail below in conjunction with the examples, so that the technical personnel of the relevant technical field can understand the present invention. It is necessary to point out here that the examples are only used to further illustrate the present invention and cannot be understood as limiting the scope of protection of the present invention. The non-essential improvements and adjustments made to the present invention by the skilled person in the relevant field according to the above invention content should still belong to the scope of protection of the present invention. At the same time, the raw materials mentioned below that are not described in detail are all commercially available products; the process steps or preparation methods that are not mentioned in detail are all process steps or preparation methods known to those skilled in the art.
[0024] Example 1
[0025] A ceramic rock slab comprises, from bottom to top, a body layer, a surface glaze layer, a pattern decoration layer and a starlight glaze layer.
[0026] The raw material components of the starlight glaze layer include, by weight: 33 parts of potassium feldspar, 27 parts of quartz, 11 parts of burned talc, 11 parts of calcite, 9 parts of Suzhou clay, 2 parts of ferric oxide, 2 parts of zinc oxide, and 2 parts of magnesite. The thickness of the starlight glaze layer is 0.8 mm.
[0027] The chemical composition of the glaze layer includes, by weight percentage: SiO2 58.80%, Al2O3 29.28%, Fe2O3 0.20%, TiO2 0.01%, CaO 0.77%, MgO 0.13%, K2O 1.48%, Na2O 3.56%, ZrO2 0.56%, ZnO 1.35%, and loss on ignition 3.86%.
[0028] The chemical composition of the green body layer includes, by weight percentage: SiO2 67.75%, Al2O3 20.09%, Fe2O3 0.41%, TiO2 0.24%, CaO 0.55%, MgO 0.86%, K2O 3.57%, Na2O 2.42%, and ignition loss 4.11%.
[0029] The method for preparing the ceramic rock plate comprises the following steps:
[0030] (1) weighing raw materials for preparing the green body layer according to the raw material ratio, preparing the powder, distributing the powder, pressing and forming the powder with a 10,000-ton press, and drying the powder to obtain the green body layer;
[0031] (2) Weigh the raw materials of the surface glaze layer and the starlight glaze layer according to the raw material ratio, mix them, perform wet ball milling, remove iron and homogenize, and obtain the surface glaze slurry and the starlight glaze slurry; then, apply the surface glaze slurry, inkjet print pattern, and starlight glaze slurry on the surface of the body layer in sequence, and form the surface glaze layer, pattern decoration layer and starlight glaze layer in sequence; put them into the kiln and fire them in a reducing atmosphere to obtain the ceramic rock plate of this embodiment. Wherein: the firing temperature system is: first increase the temperature to 1250℃ at a heating rate of 15℃ / min, keep it warm for 10min; then cool it to 850℃ at a rate of 8℃ / min, keep it warm for 35min, and finally leave the kiln and cool it naturally.
[0032] Example 2
[0033] A ceramic rock slab comprises, from bottom to top, a body layer, a surface glaze layer, a pattern decoration layer and a starlight glaze layer.
[0034] The raw material components of the starlight glaze layer include, by weight: 28 parts of potassium feldspar, 30 parts of quartz, 12 parts of calcite, 10 parts of calcite, 12 parts of Suzhou clay, 1 part of ferric oxide, 3 parts of zinc oxide, and 1 part of magnesite. The thickness of the starlight glaze layer is 0.6 mm.
[0035] The chemical composition of the glaze layer includes, by weight percentage: SiO2 58.80%, Al2O3 29.28%, Fe2O3 0.20%, TiO2 0.01%, CaO 0.77%, MgO 0.13%, K2O 1.48%, Na2O 3.56%, ZrO2 0.56%, ZnO 1.35%, and loss on ignition 3.86%.
[0036] The chemical composition of the green body layer includes, by weight percentage: SiO2 67.75%, Al2O3 20.09%, Fe2O3 0.41%, TiO2 0.24%, CaO 0.55%, MgO 0.86%, K2O 3.57%, Na2O 2.42%, and ignition loss 4.11%.
[0037] The method for preparing the ceramic rock plate comprises the following steps:
[0038] (1) weighing raw materials for preparing the green body layer according to the raw material ratio, preparing the powder, distributing the powder, pressing and forming the powder with a 10,000-ton press, and drying the powder to obtain the green body layer;
[0039] (2) Weigh the raw materials of the surface glaze layer and the starlight glaze layer according to the raw material ratio, mix them, perform wet ball milling, remove iron and homogenize, and obtain the surface glaze slurry and the starlight glaze slurry; then, apply the surface glaze slurry, inkjet print pattern, and starlight glaze slurry on the surface of the body layer in sequence, and form the surface glaze layer, pattern decoration layer and starlight glaze layer in sequence; put them into the kiln and fire them in a reducing atmosphere to obtain the ceramic rock plate of this embodiment. Wherein: the firing temperature system is: first increase the temperature to 1230℃ at a heating rate of 12℃ / min, keep it warm for 15min; then cool it to 800℃ at a rate of 8℃ / min, keep it warm for 40min, and finally leave the kiln and cool naturally.
[0040] Example 3
[0041] A ceramic rock slab comprises, from bottom to top, a body layer, a surface glaze layer, a pattern decoration layer and a starlight glaze layer.
[0042] The raw material components of the starlight glaze layer include, by weight: 33.5 parts of potassium feldspar, 25 parts of quartz, 8 parts of calcite, 12 parts of calcite, 9 parts of Suzhou clay, 2 parts of ferric oxide, 3 parts of zinc oxide, and 2.5 parts of magnesite. The thickness of the starlight glaze layer is 1.0 mm.
[0043] The chemical composition of the glaze layer includes, by weight percentage: SiO2 58.80%, Al2O3 29.28%, Fe2O3 0.20%, TiO2 0.01%, CaO 0.77%, MgO 0.13%, K2O 1.48%, Na2O 3.56%, ZrO2 0.56%, ZnO 1.35%, and loss on ignition 3.86%.
[0044] The chemical composition of the green body layer includes, by weight percentage: SiO2 67.75%, Al2O3 20.09%, Fe2O3 0.41%, TiO2 0.24%, CaO 0.55%, MgO 0.86%, K2O 3.57%, Na2O 2.42%, and ignition loss 4.11%.
[0045] The method for preparing the ceramic rock plate comprises the following steps:
[0046] (1) weighing raw materials for preparing the green body layer according to the raw material ratio, preparing the powder, distributing the powder, pressing and forming the powder with a 10,000-ton press, and drying the powder to obtain the green body layer;
[0047] (2) Weigh the raw materials of the surface glaze layer and the starlight glaze layer according to the raw material ratio, mix them, perform wet ball milling, remove iron and homogenize, and obtain the surface glaze slurry and the starlight glaze slurry; then, apply the surface glaze slurry, inkjet print pattern, and starlight glaze slurry on the surface of the body layer in sequence, and form the surface glaze layer, pattern decoration layer and starlight glaze layer in sequence; put them into the kiln and fire them in a reducing atmosphere to obtain the ceramic rock plate of this embodiment. Wherein: the firing temperature system is: first increase the temperature to 1280℃ at a heating rate of 15℃ / min, keep it warm for 15min; then cool it to 900℃ at a rate of 10℃ / min, keep it warm for 30min, and finally leave the kiln and cool naturally.
[0048] Comparative Example 1
[0049] The only difference between Comparative Example 1 and Example 1 is that the raw material components of the star glaze layer of Comparative Example 1 do not contain ferric oxide.
[0050] Comparative Example 2
[0051] The only difference between Comparative Example 2 and Example 1 is that the raw material components of the star glaze layer of Comparative Example 2 do not contain zinc oxide.
[0052] Comparative Example 3
[0053] The only difference between Comparative Example 3 and Example 1 is that the raw material components of the star glaze layer of Comparative Example 3 do not contain dolomite.
[0054] Comparative Example 4
[0055] The only difference between Comparative Example 4 and Example 1 is that the thickness of the star glaze layer in Comparative Example 4 is 0.3 mm.
[0056] Comparative Example 5
[0057] The only difference between Comparative Example 5 and Example 1 is that during the preparation of the ceramic rock slab of Comparative Example 5, the firing temperature regime is: firstly increase the temperature to 1250°C at a heating rate of 15°C / min, keep the temperature for 45 minutes, and then take out of the kiln and cool naturally.
[0058] Performance Testing
[0059] The ceramic rock plate sample prepared in Example 1 was observed under lighting conditions. Figure 1 As shown, from Figure 1 It can be seen that the glaze surface is smooth, and a large number of glittering particles are evenly distributed in the glaze layer. The brightness of the glittering particles is different, which is full of three-dimensionality and layering, presenting a better starlight shining effect.
[0060] At the same time, the ceramic rock plate samples prepared in the above Examples 1-3 and Comparative Examples 1-5 were tested for wear resistance and antifouling performance, wherein: wear resistance was tested according to the standard GB / T3810.7-2016 "Determination of wear resistance of ceramic glazed tiles"; antifouling performance was tested according to GBT 3810.14-2016 "Ceramic tile test method Part 14: Determination of antifouling". The glaze quality of each sample was observed, and the results are shown in Table 1 below.
[0061] Table 1:
[0062]
[0063] As shown in Table 1, the ceramic rock slabs prepared in Examples 1-3 have a large number of glitter particles evenly distributed on their glaze surfaces, and are rich in layers and three-dimensionality, with good starlight effects; and the glaze surfaces are transparent, delicate and smooth, see Figure 1 ; At the same time, it has excellent wear resistance and anti-fouling properties.
[0064] Compared with Example 1, since the raw material components of the starlight glaze layer do not contain ferric oxide, zinc oxide and magnesite, Comparative Examples 1-3 not only result in fewer shiny particles on the glaze surface, but also the layering, three-dimensional effect and starlight effect are not as good as those in Example 1, and the wear resistance and anti-fouling properties are also reduced.
[0065] Compared with Example 1, Comparative Example 4 has a reduced thickness of the starlight glaze layer, resulting in fewer glittering particles on the glaze surface, and no sense of layering and three-dimensionality, and a poor starlight effect; the wear resistance is also significantly reduced compared with Example 1.
[0066] Compared with Example 1, since the ceramic rock plate adopts a natural cooling system during preparation, the crystals in the starlight glaze layer fail to completely precipitate, resulting in a reduction in the number of glaze glitter particles, and the distribution is uneven, without a sense of layering and three-dimensionality, the starlight effect is poor, and the glaze surface is rough and not smooth; the wear resistance and anti-fouling properties are also inferior to Example 1.
[0067] For ordinary technicians in the technical field to which the present invention belongs, several simple deductions or substitutions can be made without departing from the concept of the present invention, without having to go through creative labor. Therefore, simple improvements made to the present invention by those skilled in the art based on the disclosure of the present invention should be within the protection scope of the present invention. The above embodiments are preferred embodiments of the present invention, and all processes similar to the present invention and equivalent changes made should belong to the protection scope of the present invention.
Claims
1. A ceramic rock plate, characterized in that: The invention comprises a body layer, a surface glaze layer, a pattern decoration layer and a starlight glaze layer in order from bottom to top. The raw materials for preparing the starlight glaze layer contain basic glaze, magnesium-containing minerals, calcium-containing minerals, ferric oxide and zinc oxide.
2. The ceramic rock plate according to claim 1, characterized in that: The magnesium-containing minerals include burnt talc and magnesite, and the mass ratio of the burnt talc to the magnesite is (4-15):
1.
3. The ceramic rock plate according to claim 1, characterized in that: The calcium-containing mineral is selected from at least one of calcite, limestone and dolomite.
4. The ceramic rock plate according to claim 1, characterized in that: The basic glaze comprises feldspar, quartz and clay, and the mass ratio of the feldspar, quartz and clay is (2-5):(2-4):
1.
5. The ceramic rock plate according to claim 1, characterized in that: The raw materials for preparing the starlight glaze layer include, by weight: 65-77 parts of basic glaze, 9-18 parts of magnesium-containing minerals, 10-15 parts of calcium-containing minerals, 1-2 parts of ferric oxide, and 1-3 parts of zinc oxide.
6. The ceramic rock plate according to claim 1, characterized in that: The chemical composition of the surface glaze layer includes, by weight percentage: SiO2 55-60%, Al2O3 28-32%, Fe2O3 0.1-0.3%, TiO2 0.01-0.02%, CaO 0.6-0.8%, MgO 0.1-0.3%, K2O 1-2%, Na2O 2-4%, ZrO2 0.5-1%, ZnO 1-3%, and ignition loss 2-5%.
7. The ceramic rock plate according to claim 1, characterized in that: The thickness of the starlight glaze layer is 0.6-1.0 mm.
8. A method for preparing a ceramic rock plate as claimed in any one of claims 1 to 7, characterized in that: The following steps are involved: (1) taking raw materials for preparing the green body layer, preparing powder, and subjecting the powder to dispensing, molding, and drying to obtain the green body layer; (2) Applying a top glaze, an inkjet-printed pattern, and a starlight glaze in sequence on the surface of the green body layer to form a top glaze layer, a pattern decoration layer, and a starlight glaze layer in sequence, and then drying and firing to obtain the ceramic rock slab.
9. The method for preparing a ceramic rock plate according to claim 8, characterized in that: The sintering atmosphere is a reducing atmosphere.
10. The method for preparing a ceramic rock plate according to claim 8, characterized in that: The firing temperature system is: firstly increase the temperature to 1230-1280°C at a rate of 10-15°C / min, keep the temperature for 10-15min; then cool down to 800-900°C at a rate of 6-8°C / min, keep the temperature for 30-40min, and finally take out of the kiln and cool naturally.